TRADE OF LIVE BROODERS OF THE BLACK TIGER SHRIMP, PENAEUS (PENAEUS) MONODON Fabricius 1798 AT VISAKHAPATNAM, ANDHRA PRADESH - Paul, Miriam; Maheshwarudu, G.; Varma, J. B. (Journal of Indian Fisheries Association, 2015)
The demand for brooders of Penaeus monodon by the hatcheries, whichare solely dependant on wild brooders for their seed production, has resultedin a vigorous fishery and trade for this species, especially along theVisakhapatnam coast. More than three hundred brooders are brought in perday for trading during the peak landing season from December to Marchevery year. The price of gravid brooders has been declining over the yearsbut on an average is about Rs. 30,000 per brooder. The total length of malebrooders ranged from 190 to 246 mm during the three years under study andfor females it varied between 210 and 330 mm. A specialized methodology fortransportation, storage and trade of P. monodon brooders has been evolvedover the years at Visakhapatnam Fishing Harbour. Concentrated exploitationof brooders from the wild and presence of pathogens in them makes a strongcase for development of specific pathogen free brooders and conservation ofwild stock.Keywords: Live brooders, black tiger shrimp, conservation, wild stock.